PENGGUNAAN TEKS OTENTIK UNTUK PENINGKATAN PEMAHAMAN DAN KETRAMPILAN MENULIS TEKS PROCEDURE KELAS IX MTsN REJOSO PETERONGAN 1 JOMBANG TAHUN PELAJARAN 2011/2012 - Asy’ariy, - (Al Tadib : Jurnal Ilmu Pendidikan, 2014)
This Classroom Action Research (CAR) is aimed at improving reading comprehension skill and writing skill of text Procedure by applying the use of authentic material or text. With two cycles, this CAR brief discussion describes the process of using authentic text in teaching both skills at grade IX MTsN Rejoso Peterongan 1 Jombang. The result of this CAR shows that the use of authentic text can improve the students’ reading comprehension skill and writing skill. It is know by the indicator that aspect of writing skill in cycles 2: (1) writing skill of text procedure 82% and there is an improvement 10,4% 2 (or 11,4% compared with cycles 1 indicator), (2) comprehension of text procedure improve 14,2% (cycles 2: 89,2%) compared with cycles 1. And (3) the most important aspect is the learning result improve 12,7% or 89,3% compared with cycles 1: 76,6%. The score is a percentage of post test of comprehension skill and assignment of writing text procedure.Keywords: Comprehension skill, writing skill, authentic text